Health care experiences among women diagnosed with gestational breast cancer. (24th March 2017) - Hammarberg, K.; Sullivan, E.; Javid, N.; Duncombe, G.; Halliday, L.; Boyle, F.; Saunders, C.; Ives, A.; Dickinson, J.E.; Fisher, J.
Abstract : Gestational breast cancer (GBC) presents many challenges for women and the clinicians who care for them. The aim of this study was to explore the health care experiences of women diagnosed with GBC to inform and improve clinical care of women in this predicament. Semi‐structured interviews were conducted with 17 women who had been diagnosed with GBC in the previous 5 years. The overarching themes for perceived quality of care were "communication" and "comprehensive care." "Communication" had two sub themes: "interdisciplinary communication" (the way health professionals from different disciplines communicated with each other about the management of the woman's care) and "patient communication" (how they communicated this to the woman). The "comprehensive care" theme incorporated three sub themes: "the spirit" (psychological care); "the mind" (information provision); and "the body" (management of treatment side effects). Women's own accounts of positive and negative experiences of GBC care provide unique and specific insights which improve understanding of their concerns and needs. The findings can inform advances in quality and efficacy of clinical care; offer guidance for obstetricians, oncologists and allied health professionals about the needs of women diagnosed with GBC and how care can be optimised; and inform the development of resources to assist women and their families.